Brucella spp. Lumazine Synthase Induces a TLR4-Mediated Protective Response against B16 Melanoma in Mice - Rossi, Andrés Hugo (2015)
Brucella Lumazine Synthase (BLS) is a highly immunogenic decameric protein which can accept the fusion of foreign proteins at its ten N-termini. These chimeras are very efficient to elicit systemic and oral immunity without adjuvants. BLS signaling via Toll-Like Receptor 4 (TLR4) regulates innate and adaptive immune responses, inducing dendritic cell maturation and CD8(+) T-cell cytotoxicity. In this work we study the effect induced by BLS in TLR4-expressing B16 melanoma. In order to evaluate the effectiveness of BLS as a preventive vaccine, C57BL/6J mice were immunized with BLS or BLS-OVA, and 35 days later were subcutaneously inoculated with B16-OVA melanoma. BLS or BLS-OVA induced a significant inhibition of tumor growth, and 50% of mice immunized with the highest dose of BLS did not develop visible tumors. This effect was not observed in TLR4-deficient mice. For treatment experiments, mice were injected with BLS or BLS-OVA 2 days after the inoculation of B16 cells. Both treatments induced significant and equal tumor growth delay and increased survival. Moreover, BLS and BLS-OVA stimulation were also effective in TLR4-deficient mice. In order to study whether BLS has a direct effect on tumor cells, B16 cells were preincubated with BLS, and after 48h, cells were inoculated. Tumors induced by BLS-stimulated cells had inhibited growth and survival was increased. In the BLS group, 40% of mice did not develop tumors. This effect was abolished by the addition of TLR4/MD2 blocking antibody to cells before BLS stimulation. Our work demonstrates that BLS immunization induces a preventive antitumor response that depends on mice TLR4. We also show that BLS generates a therapeutic effect in mice inoculated with B16 cells. Our results show that BLS acts directly in cultured tumor cells via TLR4, highly suggesting that BLS elicits its therapeutic effects acting on the TLR4 from B16 melanoma cells.